New headway English Pronunciation Course : Upper-intermediate Student's Practice Book - Bowler Bill and Cunningham Sarah (New York Oxford University Press, 1999)
This is a practical addition to the 'New Headway English Course'. It helps students to express themselves clearly and confidently by training them in the key areas of pronunciation. There is practice of individual sounds, with a guide to suitable exercises for speakers of particular languages.
Keywords: Anglais (langue) -- Prononciation. -- Anglais (langue) -- Manuels Pour Allophones